Exploring the Depths: An Overview of Penetration Testing - Yusuf, Muhammad; Suharso, Aries (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
The security of a web server from data leaks is a critical factor before creating one. Penetration testing is an attempt to exploit a computer system to find data stored within it. This review aims to provide an overview of penetration testing, highlighting its implementation scenarios, models, methodologies, and tools from various existing studies. The results of this review are expected to serve as a reference for understanding the aspects and solutions of penetration testing. The review was conducted by collecting 1,023 articles, which were evaluated based on the PRISMA method, narrowing them down to 12 articles. These 12 articles were then classified based on the tools, models, and methodologies used in penetration testing. This classification aims to provide deeper insights into the best practices for penetration testing and to identify the most effective tools and techniques for securing web servers against threats and data breaches.